Political intelligence and wisdom - Harnisch, Sebastian (Intelligence, 2022)
Political intelligence encompasses special forms of mental processes that enable an actor to influence their political environment in a goal-oriented way and allows them to find a solution to problems through flexible thinking and action. In this chapter, we begin by comparing the moral wisdom of Aristotle and the utility-oriented cunning of Machiavelli from a historical perspective. Then, the conceptions of intelligence of different theories of international relations and the foreign policy of states are discussed based on current examples. Finally, we critically reflect on the extent to which political intelligence should be re-thought in an era of a ‘broad present’ (Humbrich)—in which the importance of the past and the future is increasing in today’s conceptions of politics.
Gesehen am 26.04.2023